FILSAFAT PRAGMATISME: MENINJAU ULANG INOVASI PENDIDIKAN ISLAM - Rz. Ricky Satria Wiranata; Maragustam Maragustam; M. Sayyidul Abrori (Ta'allum: Jurnal Pendidikan Islam, 2021)
This article is motivated by the fact that educational innovation in Indonesia is still low, this is reflected in the competitiveness of Indonesian human resources which is still weak when compared to Southeast Asian countries. The presence of the theory of pragmatism is expected to be a theoretical alternative to the approach of Islamic education innovation. This article seeks to formulate the design and innovation process of Islamic Education based on qualitative research and literature studies. This article is a philosophical study as an effort to construct the process of Islamic Education innovation from the perspective of Islamic philosophy and pragmatism. This study concludes that the innovation process is a necessity. In the Islamic perspective, aqidah sohihah is the key and initial step in finding the purity of Islamic education innovation. Whereas pragmatism offers an innovative process of Islamic education based on systematic steps that begin with reflective criticism, diagnosis, inventory, reflection, testing of hypotheses, public analysis, and finally implementation.